Model-based process supervision : a bond graph approach - Samantaray, Arun K. (Springer, 2017)
Model-Based Process Supervision provides control engineers and workers in industrial and academic research establishments interested in process engineering with a means to build up a functional supervisory control environment and to use sophisticated models to get the best use out of their process data